Synthesis and Characterization of peri‐Heptacene on a Metallic Surface. Issue 23 (28th April 2022) - Biswas, Kalyan; Urgel, José I.; Ajayakumar, M. R.; Ma, Ji; Sánchez‐Grande, Ana; Edalatmanesh, Shayan; Lauwaet, Koen; Mutombo, Pingo; Gallego, José M.; Miranda, Rodolfo; Jelínek, Pavel; Feng, Xinliang; et al.
Abstract: The synthesis of long n‐ peri ‐acenes (n‐PAs) is challenging as a result of their inherent open‐shell radical character, which arises from the presence of parallel zigzag edges beyond a certain n value. They are considered as π‐electron model systems to study magnetism in graphene nanostructures; being potential candidates in the fabrication of optoelectronic and spintronic devices. Here, we report the on‐surface formation of the largest pristine member of the n‐PA family, i.e. peri ‐heptacene ( n =7, 7‐PA ), obtained on an Au(111) substrate under ultra‐high vacuum conditions. Our high‐resolution scanning tunneling microscopy investigations, complemented by theoretical simulations, provide insight into the chemical structure of this previously elusive compound. In addition, scanning tunneling spectroscopy reveals the antiferromagnetic open‐shell singlet ground state of 7‐PA, exhibiting singlet–triplet spin‐flip inelastic excitations with an effective exchange coupling ( J eff ) of 49 meV. Abstract : The successful on‐surface synthesis of pristine peri ‐heptacene (7‐PA ) reveals, after thermal activation of a 4, 5, 9, 10‐tetrakis(3‐methylnaphthalen‐2‐yl)pyrene precursor on a Au(111) via surface‐assisted oxidative ring‐closure and cyclodehydrogenation reactions, an antiferromagnetic open‐shell singlet ground state exhibiting singlet–triplet spin‐flip inelastic excitations with an effective exchange coupling of 49 meV.